Facet‐Controlled Synthetic Strategy of Cu2O‐Based Crystals for Catalysis and Sensing. Issue 10 (14th August 2015) - Shang, Yang; Guo, Lin
<x xml:space="preserve">Abstract</x> Shape‐dependent catalysis and sensing behaviours are primarily focused on nanocrystals enclosed by low‐index facets, especially the three basic facets (100, 111, and 110). Several novel strategies have recently exploded by tailoring the original nanocrystals to greatly improve the catalysis and sensing performances. In this Review, we firstly introduce the synthesis of a variety of Cu2O nanocrystals, including the three basic Cu2O nanocrystals (cubes, octahedra and rhombic dodecahedra, enclosed by the 100, 111, and 110 facets, respectively), and Cu2O nanocrystals enclosed by high‐index planes. We then discuss in detail the three main facet‐controlled synthetic strategies (deposition, etching and templating) to fabricate Cu2O‐based nanocrystals with heterogeneous, etched, or hollow structures, including a number of important concepts involved in those facet‐controlled routes, such as the selective adsorption of capping agents for protecting special facets, and the impacts of surface energy and active sites on reaction activity trends. Finally, we highlight the facet‐dependent properties of the Cu2O and Cu2O‐based nanocrystals for applications in photocatalysis, gas catalysis, organocatalysis and sensing, as well as the relationship between their structures and properties. We also summarize and comment upon future facet‐related directions.